DEVELOPING STUDENTS’ VOCABULARY MASTERY THROUGH VIDEO GAME - Dian Saputra (Universitas Muhammadiyah Sorong, 2017)
The objective of this study was trying to analyze the impact of using video game in developing student’s vocabulary mastery. The method of this study was quantitative. The design of the research was based on the experimental study. Pre-test and post-test was given to 37 students of class H fifth semester of Sorong Muhammadiyah University. Score of the test was divided into five categories, they were very good, good, fairly, poor and very poor. The mean score of pre-test was 6, 51 in fairly category and the mean score of post-test was 8, 5 in very good category. It showed that the mean score of test after given the treatment was higher than test before given the treatment. The result of the t-test showed that played video games gave a significant effect on the students’ vocabulary mastery. The result of t-test was higher than t table (8, 96 > 1.68830).